Insomnia in childhood and adolescence: clinical aspects, diagnosis, and therapeutic approach - Magda Lahorgue Nunes; Oliviero Bruni (Elsevier, 2015)
Objectives: To review the clinical characteristics, comorbidities, and management of insomnia in childhood and adolescence. Sources: This was a non-systematic literature review carried out in the PubMed database, from where articles published in the last five years were selected, using the key word "insomnia" and the pediatric age group filter. Additionally, the study also included articles and classic textbooks of the literature on the subject. Data synthesis: During childhood, there is a predominance of behavioral insomnia as a form of sleep-onset association disorder (SOAD) and/or limit-setting sleep disorder. Adolescent insomnia is more associated with sleep hygiene problems and delayed sleep phase. Psychiatric (anxiety, depression) or neurodevelopmental disorders (attention deficit disorder, autism, epilepsy) frequently occur in association with or as a comorbidity of insomnia. Conclusions: Insomnia complaints in children and adolescents should be taken into account and appropriately investigated by the pediatrician, considering the association with several comorbidities, which must also be diagnosed. The main causes of insomnia and triggering factors vary according to age and development level. The therapeutic approach must include sleep hygiene and behavioral techniques and, in individual cases, pharmacological treatment. Resumo: Objetivos: Revisar as características clinicas, as comorbidades e o manejo da insônia na infância e adolescência. Fonte dos dados: Revisão não sistemática da literatura realizada na base dados PubMed,onde foram selecionados artigos publicados nos últimos 5 anos, selecionados com o uso da palavra chave insônia e o filtro faixa etária pediátrica. Adicionalmente foram também incluídos artigos e livros texto clássicos da literatura sobre o tema. Síntese dos dados: Na infância existe predomínio da insônia comportamental na forma de distúrbio de início do sono por associações inadequadas e/ou distúrbio pela falta de estabelecimento de limites. Na adolescência a insônia está mais associada a problemas de higiene do sono e atraso de fase. Transtornos psiquiátricos (ansiedade, depressão) ou do neurodesenvolvimento (Transtorno do déficit de atenção, autismo, epilepsias) ocorrem com frequência em associação ou como comorbidade do quadro de insônia. Conclusões: A queixa de insônia nas crianças e adolescentes deve ser valorizada e adequadamente investigada pelo Pediatra, levando em consideração a associação com diversas comorbidades, que também devem ser diagnosticas. As causas principais de insônia e fatores desencadeantes variam de acordo com a idade e nível de desenvolvimento. A abordagem terapêutica deve incluir medidas de higiene do sono e técnicas comportamentais, e em casos individualizados tratamento farmacológico. Keywords: Insomnia, Sleep disorders, Childhood, Adolescence, Palavras-chave: Insônia, Distúrbios do sono, Infância, Adolescência